2018
DOI: 10.5114/areh.2018.76988
|View full text |Cite
|
Sign up to set email alerts
|

The influence of total hip arthroplasty on patients’ disability

Abstract: Introduction: Hip osteoarthritis manifests itself with pain, limitation of the range of motion, weaker muscles and pathological gait pattern. Total hip arthroplasty is a treatment of choice which leads to pain relief and improvement in patients' functioning. The aim of the work was to assess the influence of total hip arthroplasty on the reduction in patients' disability. Material and methods: The study group included 30 patients aged 62.53 ± 12.79. Mean body height was 168.03 ± 8.83 cm, while mean body mass w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Before the procedure, it was 37.07 points; after the procedure, it was 74.93 points. A positive correlation was confirmed between the age of the subjects and the HHS result, and hip arthroplasty significantly reduced the patients' disability three months after the surgery [15]. In addition, Bodys-Cupak et al [16] observed a clear decrease in disability in the group of "medium-severe" patients, from 31% before surgery to 7% after surgery.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Before the procedure, it was 37.07 points; after the procedure, it was 74.93 points. A positive correlation was confirmed between the age of the subjects and the HHS result, and hip arthroplasty significantly reduced the patients' disability three months after the surgery [15]. In addition, Bodys-Cupak et al [16] observed a clear decrease in disability in the group of "medium-severe" patients, from 31% before surgery to 7% after surgery.…”
Section: Discussionmentioning
confidence: 78%
“…Hip arthroplasty results in reduced disability of patients according to Szczepłek et al [15]. The average HHS improved two-fold.…”
Section: Discussionmentioning
confidence: 97%
“…The consequence of this condition is a gradual reduction of motor activity and the creation of compensatory movement patterns in the affected area that cause a disturbance in the biomechanics of the entire body. Among all human joints, the hip joint is most commonly affected by this condition, causing the most therapeutic problems [2,5,24,38].…”
Section: Discussionmentioning
confidence: 99%
“…With the onset of joint pain, patients tend to spare the affected limb, resulting in further limitation of range of motion and subsequent contractures and muscle atrophy. These disorders significantly reduce the patient's activities of daily living and noticeably decrease their quality of life [9,17,18,27,38].…”
Section: Introductionmentioning
confidence: 99%